MANAJEMEN PEMBIAYAAN DAN IMPLIKASI TRADISI RITUAL TERHADAP MASYARAKAT HINDU DI BALI (STUDI DI DESA APUAN, KABUPATEN TABANAN) - nyoman bontot (Satya Sastraharing : Jurnal Manajemen, 2019)
Abstract A lot of ceremonial activities performed in Bali costs a lot of time. In addition, a lot of manpower and money are also needed to prepare offerings (upakara/banten). Foods (festivities) should also be prepared for those living around the temple (relatives), as can be seen from what is performed by the Hindus living at Apuan Traditional Village, Baturiti District, Tabanan Regency. The rituals (yajnya) performed which are not well based on the Hindu teaching may lead to poverty as the recently developing discourse. If rituals repeatedly performed caused the Hindus in Bali to be poor, they would certainly not perform them. The fact shows that the Hindus in Bali keep performing them, and that they have performed them more intensively. In Bali the rituals (yajna) are performed based on (1) the Tri Rna teaching which is described in the book Manawa Dharmasastra VI.35, in which it is stated that PancaYajna (five types of religious rituals) are performed to pay for the moral debts (Tri Rna), namely DewaRna, PitraRna, and RsiRna; (2) what is taught in Bhagawad Gita from III-10 to III-6 that God has created human beings through MahaYajna; (3) the palm leaf Manuscript of DewaTattwa, which contains the guidelines for the performance of PancaYajna. Three funding models are employed in the performance of the religious rituals (yajna); they are (1) guna kaya, namely the family income; (2) patus, namely the donation obligatorily donated by the villagers (kramadesa) the amount of which is based on the agreement made; and (3) aban-aban, namely the donation voluntarily donated by the villagers and their relatives. The rituals are performed by helping one another (gotongroyong). If calculated, the value of helping one another exceeds the value of the three afore mentioned funding models. The implications of the performance of the religious rituals in Bali are that (1) it strengthens the unity of the Hindus; (2) it improves their managerial skill; (3) it improves their work ethics; (4) it supports their financial planning and saving model; and (5) it creates job/business opportunities. Keywords: funding managementl, ritual tradition, Hindu society